Visionary Principal Leadership in Driving School-Based Management in the 3T Region of Morotai Island - Fahmi Jaguna; Jasmal Martora; Irawati Sabban; Abd Sarman Sibua; Alfatah Sibua (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
School principal leadership is a strategic determinant of the successful implementation of School-Based Management (SBM), particularly in primary schools located in Indonesia’s Remote, Frontier, and Outermost (3T) regions, where educational development is constrained by limited resources and restricted access to quality educational services. This study aims to examine the characteristics of visionary school leadership, the strategies employed to drive SBM implementation, and their implications for educational quality and school autonomy at SD Muhammadiyah 1 Pulau Morotai. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, participant observation, and document analysis involving the principal, teachers, the school committee, parents, and the school supervisor. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while research trustworthiness was ensured through source, method, and time triangulation, member checking, and an audit trail. The findings reveal that visionary leadership is reflected in the principal’s ability to formulate and communicate a shared vision, foster a collaborative school culture, optimize local resources, and strengthen partnerships with the Muhammadiyah organization, Save the Children, Stimulant Institute, and the Faculty of Teacher Training and Education of Universitas Pasifik Morotai. These practices enhance SBM implementation, improve teachers’ professional capacity, increase community participation, and strengthen school autonomy. The study contributes to the literature by proposing an Island-Based Collaborative Visionary Leadership Model, demonstrating that effective SBM in 3T regions depends not only on managerial competence but also on social capital, institutional collaboration, and context-responsive educational governance tailored to island communities.